ANALISIS PENGARUH MODAL, LAMA USAHA, PEMILIHAN LOKASI, JAM KERJA TERHADAP PENDAPATAN PELAKU USAHA MIKRO PADA DESTINASI WISATA NAGARI TUO PARIANGAN KABUPATEN TANAH DATAR - Ilham Syukmatullah; Novera Martilova (ADISAM PUBLISHER, 2024)
The research aims to determine and analyze capital, length of business, choice of location and working hours on the income of micro business actors in the Nagari Tuo Pariangan tourist destination, Tanah Datar Regency. The data analysis method is a quantitative field research method. Sampling used a simple random sampling technique using judgment sampling from the total population by giving questionnaires directly to micro business actors. Meanwhile, the data analysis technique uses multiple linear regression analysis. The research results show that capital does not have a significant effect on the income of micro entrepreneurs in the Nagari Tuo Pariangan destination. Length of business does not have a significant effect on the income of micro business actors in the Nagari Tuo Pariangan destination. The choice of location does not have a significant effect on the income of micro business actors in the Nagari Tuo Pariangan destination. Meanwhile, working hours have a significant effect on the income of micro business actors in the Nagari Tuo Pariangan destination. Simultaneously there is an influence between capital, length of business, choice of location and working hours on the income of micro business actors in the Nagari Tuo Pariangan destination